Thermal and Flow Analysis of the Helical Coil Heat Exchanger Used in an Aqueous Solution of Ammonium Nitrate Solubility (ANSOL) with 20% H2O and 80% AN - Nogueira, Élcio (Current Approaches in Science and Technology Research Vol. 12, 2021)
The case study is about obtaining the flow rate and saturation temperature of steam that makes it possible to heat a solution of water and ammonia nitrate (ANSOL) in a shell and helical coil tube heat exchanger, within a time interval, without that the crystallization of the ANSOL solution occurs. The desired production per batch of the solution is 5750 kg in 80 minutes. The analysis uses the concepts of efficiency and effectiveness to determine the heat transfer rate and temperature profiles that satisfy the imposed condition within a certain degree of safety and with the lowest possible cost in steam generation. Intermediate quantities necessary to reach the objective are the Reynolds number, Nusselt number, and global heat transfer coefficient for the shell and helical coil tube heat exchanger. Initially, the water is heated for a specified period and, subsequently, the ammonium nitrate is added to a given flow in a fixed mass flow rate.